SEJARAH MENJAWAB TANTANGAN: MENGGAGAS MASA DEPAN DI ERA DIGITAL - Syaifulloh, Muhammad; Fitriana, Desy (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This article delves into the role of history in addressing future challenges, particularly concerning the advancements in artificial intelligence and digital transformation. By detailing the impact of history on understanding and adaptation, the article offers practical insights to guide us through the forthcoming changes.